PASANG SURUT KEKUASAAN PRESIDEN REPUBLIK INDONESIA BERDASARKAN UUD 1945 SEBELUM DAN SESUDAH AMANDEMEN - ISMAIL, M. (GANEC SWARA, 2018)
On August 18, 1945, for the first time the President and Vice President were elected by PPKI. In the early days of the administration, the power of the President in running the government was not only based on Articles 4.5,10,11,12,13,14 and 15 of the 1945 Constitution, but also based on Article IV of the Transitional Rules which read "Before the MPR, DPR and DPA were formed all power run by the President with the help of a National Committee. Based on the provisions of the provisions of Article IV, the President has enormous power. So that the President can legitimately act as a dictator, because the presence of the Central National Committee which has a role in assisting the President's task cannot at all be interpreted as a reduction in the power of the President. The history of the Republic of Indonesia has proven that the 1945 Constitution has undergone a very rapid development and within two months of the 1945 Constitution there has been a change in the state administration practices of the Republic of Indonesia, after the issuance of the Decree of the Vice President Number X dated October 16, 1945.From the description above, actually it has not carried out the articles of the 1945 Constitution, because the article used is precisely the article of the Transitional Rules. For example, the President and Vice President according to the 1945 Constitution should be elected by the MPR in accordance with Article 6 paragraph (2), but chosen by PPKI according to Article III of the Transitional Rules. This is certainly understandable, because this is the first time in delivering a country. President Soekarno's power with democracy was dreamed up not to uphold the values of popular sovereignty, but what was upheld was the power of the leader and even very tragically Sukarno was appointed as President for life through the MPRS decree and this included the violation of the 1945 Constitution. the political stage replacing Soekarno's violation of the 1945 Constitution was repeated, because the 1945 Constitution could not be formed by anyone.